Coulomb Stress Change of Mw 7.5 Palu-Donggala Earthquake, Sulawesi (28 September 2018) - Adhi Wibowo; Pepen Supendi; Andri D. Nugraha (Himpunan Ahli Geofisika Indonesia (HAGI), 2020)
The Mw 7.5 Palu earthquake that occurred in Palu-Central Sulawesi, Indonesia, on September 28, 2018, accompanied by the tsunami and liquefaction caused casualties and building damage in the city of Palu and its surroundings. One month later, a series of earthquakes swarm occurred in Mamasa, West Sulawesi. In this study, coulomb stress were calculated using a half-space elastic model in a square plane which is assumed to be homogeneous isotropy to analyze whether there is a relationship between earthquakes that occur in Palu and earthquakes swam in the coulomb stress field changes. The results show that the area that experienced a stress reduction predominantly towards the north and south of the mainshock hypocenter, while the aftershocks were at an increase in coulomb stress changes, so that the Mamasa earthquakes swarm probably have been triggered by the Palu earthquake.